Pengaruh Manajemen Kesiswaan dan Kurikulum terhadap Prestasi Madrasah Aliyah Tmi Putri Al-Amien Prenduan Sumenep Madura - Dini Nur Jannah; Qowaid Qowaid; M Faqihudin (Jurnal Dirosah Islamiyah, 2019)
In article 35 paragraph 2 that the National education system is mandated to develop education through sustainable management which includes improving the quality of curriculum development, education personnel, facilities and infrastructure, management (management) and empowerment. Student management and curriculum management is one of the existing management in a school. Schools continue to try to improve the quality of education including student development and curriculum improvement. The institution has a good strategy so that it can achieve both academic and non-academic achievements. The purpose of this study was to determine the effect of student management on the achievement of the TMI Madrasah Aliyah School (Tarbiyatul Muallimien Al-Islamiyah) female Al-Amien Prenduan. Know there any influence of curriculum management on the achievement of the TMI Madrasah Aliyah School (Tarbiyatul Muallimien Al-Islamiyah) female Al-Amien Prenduan. Knowing the effect of student management and curriculum management on the achievements of the TMI (Tarbiyatul Muallimien Al-Islamiyah) Islamic Al-Islamiyah School of female Al-Amien Prenduan. This research is quantitative descriptive type. Research location at TMI (Tarbiyatul Muallimien Al-Islamiyah) female Al-Amien Prenduan. The data source in this study is the teacher who has an active role in the school. The data collection technique used was a questionnaire. The results showed that student management X1 and curriculum management variable X2 significant value 0,000 <0.05 on the school achievement variable Y then there was the influence of variables X1 and X2 on the variable Y. This was indicated by a score of 35.9% in either category.